Ajay’s Law - Ramshaw, Sara (Critical Studies in Improvisation / Études critiques en improvisation)

(untitled) (University of Guelph College of Arts, 2025)
Sara Ramshaw reflects on her relationship with Ajay Heble, especially through the lens of her research in the field of Law.